Gender differences in tuberculosis incidence rates—A pooled analysis of data from seven high-income countries by age group and time period - Peer, Victoria; Schwartz, Naama; Green, Manfred S. (Frontiers in Public Health, 2023)
Abstract Introduction. Gender differences in the incidence rates for tuberculosis are occasionally reported. However, the magnitude and consistency of the differences by age group, in different populations and over extended time periods, are not clear. Materials and methods. We obtained national data from seven countries from open access internet sites or personal communications with official representatives. We computed the male to female incidence rate ratios (IRRs) by country and years for every age group and pooled these ratios using meta-analytic methods. Meta-regression analysis was performed to estimate the contribution of age, country and calendar years to the variation in the IRRs. Results. In the age groups <1, 1-4, 5-9 and 10-14, the pooled male to female IRRs (with 95% CI) were: 1.21 (1.05,1.40), 0.99 (0.95,1.04), 1.01 (0.96,1.06) and 0.83 (0.77, 0.89) respectively. In the age groups 15-44, 45-64 and 65+, incidence rate were significantly higher in males, with IRRs of 1.25 (1.16, 1.35), 1.79 (1.56, 2.06) and 1.81 (1.66, 1.96) respectively. Meta-regression analysis revealed that age significantly contributed to the variation in the IRRs. Conclusions. There were gender differences in the incidence rates for tuberculosis, with higher rates in males age less than one, no significant differences in age 1-9 and higher rates in males older than 15. The only excess in females was in the age group 10-14. The age-related gender differences in tuberculosis incidence rates observed over a number of countries, indicate the importance of including sex as a biological variable when assessing the risk factors for tuberculosis.